Synthesis of islamic epistemology "bayani, burhani, and irfani" as a foundation for the development of contemporary scientific integration - Mohammad Syaifuddin; Muhlisin; Slamet Untung; Amat Zuhri; Nur Khikmah; Thoyibah; Arditya Prayogi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The crisis of modern science, characterized by the fragmentation of knowledge and the separation of scientific inquiry from ethical and spiritual values, has intensified the need to revisit Islamic epistemology as an integrative framework of knowledge. This study aims to examine the characteristics and dialectical relationships of the three major paradigms of Islamic epistemology, namely bayani, burhani, and irfani, as the foundation for developing a holistic scientific worldview grounded in tawḥīd al-‘ilm. This research employed a qualitative philosophical approach using conceptual, historical, and comparative analyses of classical and contemporary Islamic intellectual works, particularly those of al-Jabiri, al-Farabi, Ibn Sina, alGhazali, Suhrawardi, al-Attas, and Seyyed Hossein Nasr. The findings indicate that bayani represents revelation-based textual rationality, burhani emphasizes logical and empirical reasoning, while irfani highlights spiritual intuition and inner illumination as pathways to attaining truth. The study further reveals that these three epistemological paradigms are not contradictory but complementary and mutually reinforcing within the Islamic intellectual tradition. Their synthesis forms a comprehensive epistemological framework capable of integrating revelation, rationality, and spirituality into a unified system of knowledge. The study concludes that the integration of bayani, burhani, and irfani offers an alternative paradigm for reconstructing contemporary science that is intellectually rigorous, ethically grounded, and spiritually oriented, thereby contributing to the development of a more humane and value-based scientific civilization.